Computational Design of Rare-Earth Reduced Permanent Magnets. (February 2020) - Kovacs, Alexander; Fischbacher, Johann; Gusenbauer, Markus; Oezelt, Harald; Herper, Heike C.; Vekilova, Olga Yu.; Nieves, Pablo; Arapan, Sergiu; Schrefl, Thomas
Abstract: Multiscale simulation is a key research tool in the quest for new permanent magnets. Starting with first principles methods, a sequence of simulation methods can be applied to calculate the maximum possible coercive field and expected energy density product of a magnet made from a novel magnetic material composition. Iron (Fe)-rich magnetic phases suitable for permanent magnets can be found by means of adaptive genetic algorithms. The intrinsic properties computed by ab initio simulations are used as input for micromagnetic simulations of the hysteresis properties of permanent magnets with a realistic structure. Using machine learning techniques, the magnet's structure can be optimized so that the upper limits for coercivity and energy density product for a given phase can be estimated. Structure property relations of synthetic permanent magnets were computed for several candidate hard magnetic phases. The following pairs (coercive field (T), energy density product (kJ·m −3 )) were obtained for iron-tin-antimony (Fe3 Sn0.75 Sb0.25 ): (0.49, 290), L10 -ordered iron-nickel (L10 FeNi): (1, 400), cobalt-iron-tantalum (CoFe6 Ta): (0.87, 425), and manganese-aluminum (MnAl): (0.53, 80).